Peer production by persons with disabilities – opening 3D-printing aids to everybody in an inclusive MakerSpace. Issue 1 (8th April 2020) - Bosse, Ingo Karl; Pelka, Bastian
Abstract : Purpose: People with disabilities (PWD) produce aids using 3D printing in an inclusive MakerSpace in Germany. This study aims to demonstrate the pathways enabling people with disabilities to be "makers" of aids, creating a "medium-quality market". Design/methodology/approach: This study conceptualizes the foundation of the MakerSpace as a social innovation and traces supporting and hindering factors on three different layers: normative, structural and functional contexts. Findings: 3D printing can empower PWD to design and construct aids by themselves. The emerging "medium-quality" market offers potentials for availability for individualized aids. The design-thinking method used and the developed scalable approach empower PWD to create aids that best meet their own needs. The study found three arguments for printing aids that involve 3D printers: "New": objects that are not available without a 3D printer. "Better": objects that are available through established channels but were produced either more cheaply, quickly or on a more individualized level. "More": objects that are available through other channels, but where 3D printing allows more of them to be produced for more people. Research limitations/implications: The qualitative study has limitations because of sample size and context dependency. Research has only been carried out in Germany. Future research should be conducted in other countries to generalize the results. Practical implications: The article allows to understand the emergence of a new market for aids. It can steer producers (including PWD or sheltered workshops) in producing new aids and making them available to more people. Social implications: Understanding the functioning of the "new market for aids" can boost the accessibility of aids. Empowering PWD to produce aids can support their independence, self-determination and self-esteem. Supporting PWD to become producers of aids can support them in becoming experts and boost the quality and availability of aids. Originality/value: All data presented has been collected by the authors.